Becoming Dr. Seuss : Theodor Geisel and the making of an American imagination - Jones, Brian Jay (Dutton, 2019)
"The definitive, fascinating, all-reaching biography of Dr. Seuss. Dr. Seuss is a classic American icon. His work has defined our childhoods and the childhoods of our own children. More than twenty-five years after his death, his books continue to find new readers, now grossing over half a billion dollars in sales. His whimsical illustrations and silly, simple rhymes are timeless favorites because, quite simply, he makes us laugh. Theodor Geisel, however, led a life that goes much deeper than the prolific and beloved children's book author. In fact, the allure and fascination of Dr. Seuss begins with this second, more radical side. He had a successful career as a political cartoonist, and his political leanings can be felt throughout his books--remember the environmentalist of The Lorax? Geisel was a complicated man, who introduced generations to the wonders of reading while teaching young people about empathy and how to treat others well"--